Enhanced Optical Delay Line in Few-Mode Fiber Based on Mode Conversion Using Few-Mode Fiber Bragg Gratings - Zaini, Muhammad Khairol Annuar; Lee, Yen Sian; Lim, Kok Sing; Nazal, Nurul Asha Mohd; Yang, Hang Zhou; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2018)
In this paper, we proposed an optical delay system based on a segment of few-mode fiber (FMF) and two FMF Bragg gratings (FMFBGs). The FMFBGs at both the ends of the FMF segment that serve as selective mode converters enable the pulse stream to double pass the FMF segment twice via access to the optical path length on LP11 mode in the FMF. The induced time delay by the proposed system is approximately four times the time delay of a single pass in the FMF segment. The proposed system has opened up a new horizon in the optical buffering technology for an optical communication system.